Enhancing Cultural Competence in Counselor Education through Sociolinguistic Awareness - Jessica Haas; Diane D. Walsh; Marisa Marroquin (Teaching and Supervision in Counseling, 2024)
Language plays a central role in building a therapeutic working alliance. Language is essential in building trust, conveying empathy, and creating shared meaning between counselors and clients. Nevertheless, language can equally harm the working alliance if used insensitively or without awareness of cultural and social differences. Sociolinguistic awareness emphasizes the interpretational nature of language and how it can unintentionally perpetuate discrimination against marginalized identities. Counselor educators can utilize sociolinguistic principles to model and teach the significance of language in counseling and its relationship to multicultural competency and cultural humility. The article highlights how clients' language may connect to their social perspective and identity expression and how language can be used by the counselor to avoid misunderstandings, microaggressions, or aggressions.
Keywords: cultural humility; multicultural competency; sociolinguistics; language; therapeutic alliance